2011
DOI: 10.1136/ard.2010.147793
|View full text |Cite
|
Sign up to set email alerts
|

The association between smoking and the development of psoriatic arthritis among psoriasis patients

Abstract: Smoking may be inversely associated with PsA among psoriasis patients. This association is not present among HLA-C*06-positive individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 24 publications
5
52
2
3
Order By: Relevance
“…Smoking is a possible risk factor for developing PsA, but results are conflicting 7 8. However, little is known about the impact of smoking on disease activity and TNFi treatment response in PsA 9–13.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is a possible risk factor for developing PsA, but results are conflicting 7 8. However, little is known about the impact of smoking on disease activity and TNFi treatment response in PsA 9–13.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies suggest that psoriasis patients who are smokers (but not those who consume alcohol) may be less likely to develop psoriatic arthritis, we are unaware of other studies that have compared the frequency of smoking and alcohol intake in both these groups of patients [39]. Our findings are important because they demonstrate how prevalent these habits are in patients with psoriatic disease and emphasize the importance of counseling patients about these habits.…”
Section: Discussionmentioning
confidence: 52%
“…28 Evidence for smoking is more conflicting, with at least 2 studies finding smoking a positive risk factor 14,29 and another reporting that smoking is protective. 30 A population-based study using The Health Improvement Network (THIN) database reported a greater incidence rate of psoriatic arthritis in a psoriasis population with increasing body mass index. 31 The severity of psoriasis seems unlikely to be a major risk factor for developing psoriatic arthritis, as most patients with psoriatic arthritis have low Psoriasis Area Severity Index (PASI) scores.…”
Section: Risk Factors For Psoriatic Arthritis In Psoriasis Clinical Amentioning
confidence: 99%